PENGUJIAN KEKUATAN DIELEKTRIK MINYAK SAWIT DAN MINYAK CASTROL MENGGUNAKAN ELEKTRODE BOLA-BOLA DENGAN VARIASI JARAK ANTAR ELEKTRODE DAN TEMPERATUR - Umiati, Ngurah Ayu Ketut (Transmisi, 2009)
In this paper we explained the breakdown voltage testing that has been done on two dielectric liquid, castrol oil and palm oil using ball to ball electrode. This research observed the effect analysis of electrode gap distance to breakdown voltage, relation between temperature and breakdown voltage, liquid viscocity and breakdown voltage, and increasing temperature to the liquid viscocity. As the laboratory testing result, the breakdown voltage had proportional relation with the electrode gap distance. Viscocity of the liquid influence with its molecular structure and temperature. The liquid dieletricity depend on the electric field exposed and its viscocity. Palm oil has better dielectricity than castor oil in all distance variation and temperature. As the dielectric material must have big breakdown voltage value, the palm oil seen to have this feasibility according to its breakdown voltage 33,060 kV at gap distance 3 mm. Keywords: breakdown voltage, temperature, viscocity, electrode gap distance, dielectric, castor oil, palm oil.